Вітчизняний та зарубіжний досвід розвитку систем менеджменту ре-креаційних підприємств - Пшик-Ковальська, О. О.; Гой, Ю. Р.; Pshyk-Kovalska, O. O.; Goi, Y. R. (Видавництво Львівської політехніки, 2024)
Проаналізовано вітчизняний та зарубіжний досвід розвитку систем менеджменту рекреаційних підприємств. Зарубіжний досвід розглянуто через призму європейського, американського та азіатського підходів до розвитку систем менеджменту рекреаційних підприємств. На засадах порівняння вітчизняних та зарубіжних підходів до управління рекреаційними підприємствами було виявлено їхні переваги та недоліки. Ідентифіковано ключові проблеми вітчизняної системи менеджмент. Розроблено рекомендації щодо адап- тації успішних зарубіжних практик менеджменту до умов українського ринку рекреацій- них послуг.

The article presents a comprehensive examination of domestic and international experiences in developing management systems for recreational enterprises. A thorough comparative analysis was conducted, focusing on approaches to managing recreational enterprises in Europe (with case studies from Italy, Spain, and France), the United States, and Asia (exemplified by Japan, Singapore, and South Korea). This analysis facilitated the identification of strengths, weaknesses, and both shared and distinctive features when compared to domestic practices. The research highlights several common trends in the management of recreational enterprises globally. These include the increasing significance of information technologies in operational management, a growing emphasis on environmental sustainability, and a sharp focus on enhancing service quality and overall customer experience. These shared characteristics underscore the global nature of certain challenges and opportunities in the recreational sector. Through an extensive review of literary sources, the study identified key issues confronting Ukrainian recreational enterprises. The domestic management system is notably characterized by inadequate automation, insufficient integration of environmental management practices, and limited utilization of modern analytical tools. In stark contrast, foreign systems exhibit advanced levels of process automation, successful implementation of Big Data technologies, and innovative applications of robotics and artificial intelligence. Based on these findings, the study concludes that there is a pressing need to adapt successful international practices to the unique conditions of the Ukrainian recreational services market. The article proposes a series of recommendations aimed at enhancing management practices. These include the strategic implementation of innovative technologies, concerted efforts to improve service quality, the development of robust partnership networks, and the integration of comprehensive environmental management systems. The authors argue that implementing these recommendations will significantly boost the competitiveness of domestic recreational enterprises in the global market. Moreover, these improvements are expected to play a crucial role in preserving human capital during challenging economic periods, a factor of particular importance in the current Ukrainian context. Looking ahead, the article outlines promising avenues for future research. These include in-depth investigations into the nuances of implementing cutting-edge technologies such as Big Data analytics, artificial intelligence systems, and robotics within the management frameworks of recreational enterprises. Such studies will be instrumental in guiding the sector’s technological evolution and ensuring its longterm sustainability and competitiveness.
Domestic and foreign experience in the development of management systems of recreation enterprises
Keywords: менеджмент; рекреаційні підприємства; зарубіжний досвід; інно- вації; екологічний менеджмент; автоматизація; management; recreational enterprises; foreign experience; innovations; environmental management; automation; 338.48-6; 640.43